The Influence of Influencers and Brand Awareness on Purchase Decisions in MSMEs (Amaryllis Hijab) - Megawati Beddu; Ismah Rustam; Andi Alfianto Anugrah Ilahi; Irawati Nur; Imron Burhan (International Journal of Economics, Business and Innovation Research, 2025)
Small and Medium Enterprises (SMEs) as drivers of the Indonesian economy often face marketing constraints due to limited resources, resulting in low consumer awareness of their products. The utilization of influencer marketing and brand awareness strengthening proved to be an effective solution to enhance purchasing decisions, particularly for Amaryllis Hijab SMEs in the competitive Muslim fashion industry. This study analized the influence of both influencers and brand awareness to provide strategic contributions for the development of digital marketing in SMEs. This research aimed to determine the partial and simultaneous influence of Influencer and Brand Awareness on purchasing decisions in MSMEs (Amaryllis Hijab). The data analysis method used is quantitative descriptive analysis. The data analysis technique employed was multiple regression analysis using SPSS for Windows 30.0. The data utilized in this research was primary data, sourced from questionnaires filled out by respondents. The results of this research indicated that Influencer partially influenced purchasing decisions in MSMEs (Amaryllis Hijab), with a t count​ value of (2.800) > ttable​ (2.002) and a significance value of 0.007 < 0.05. And Brand Awareness partially influenced purchasing decisions in MSMEs (Amaryllis Hijab), with a tcount​ value of (3.842) > ttable​ (2.002) and a significance value of <0.001 < 0.05. Influencer and Brand Awareness simultaneously influenced purchasing decisions in MSMEs (Amaryllis Hijab), with an f count​ value of (41.226) > ftable​ (3.15) and a significance of <0.001 < 0.05.